omparison of Disability Cases According to National Regulations and the American Medical Associatıon Permanent Disability Assessment Guide: National and International Guides on Disability Calculation - Aytuğ, Şahnur Serap; Gamsız Bilgin, Nursel (The Bulletin of Legal Medicine, 2022)
Objective: International classification of functioning, disability and health (ICF) was prepared by the World Health Organization to create a standard language for the definition and measurement of health and health-related states. ICF classification collects disease and disability situation sunder 3 titles as organ/system structure sand functions, activity limitations. The guide prepared by the American Medical Association has been prepared based on ICF terminology. AMA guideline calculates the disability rating according to the effects of the person’s daily and social life activities. Methods: It is aimed to compare the regulations used in our country with the AMA guideline over the calculated disability rates. The disability rates of 315 cases who developed extremity injuries as a result of traffic accidents between 2018 and 2019 were calculated according to 3 regulations. The cases were analyzed in terms of gender, age at the time of the incident, type of accident, time between the incident and admission, injury sites, the clinics for which consultation was requested, whether the operation was performed and the complications that occurred. Results: 81.9% of the cases were male, the mean age was 31.14 years, when we look at the disability rate values, the highest disability rates is calculated according to the SGK Regulations and the lowest disability rates calculated according to AMA guideline. Conclusion: AMA guideline has been prepared in detail and clearly for extremity disability calculation and we think that it should be in routine practice to prevent loss of rights.